Risk factors for complications in peripheral intravenous catheters in adults: secondary analysis of a randomized controlled trial - Derdried Athanasio Johann; Mitzy Tannia Reichembach Danski; Stela Adami Vayego; Dulce Aparecida Barbosa; Jolline Lind
ABSTRACT Objective: analyze the risk factors linked to complications in peripheral intravenous catheters. Method: secondary data analysis of a randomized controlled trial with 169 medical and surgical patients placed in two groups, one with integrated safety catheter (n=90) and other using simple needle catheter (n=79), with three months follow-up time. Results: the risk factors that raised the odds of developing complications were: hospitalization between 10-19 days (p=0.0483) and 20-29 days (p=0,0098), antimicrobial use (p=0.0288) and use of fluid solutions (p=0.0362). The 20 Gauge lowered the risks of complications (p=0.0153). Multiple analysis showed reduction of risk for the 20 Gauge (p=0.0350); heightened risk for solutions and fluids (p=0.0351) and use of corticosteroids (p=0.0214). Conclusion: risk factors linked to complications in peripheral intravenous catheters were: hospitalization periods between 10-29 days, antimicrobial infusion, solutions and fluids and corticosteroids. Regarding complications, 20 Gauge is a protecting factor compared with 22. Brazilian Clinical Trials Registry: RBR-46ZQR8.